Measuring the Benefits of the Skill Academy’s Online Training Platform - Putro, Endi; Averil, Juditha (Journal of Information System and Informatics, 2023)
The research purpose is to prove the truth of an internal survey of 96,406 users of the Academy Skills platform. The results of the survey stated that after participating in the training the user felt an increase in skills. Verification of the correctness of the survey uses a combination of the Delone and McClean (DM) models and the Technology-to-Performance Chain (TPC) model which has 5 constructs: System quality, information quality, service quality, task-Technology Fit, and Net Benefit. The method used in this study is a quantitative method through the development of identified constructs. Quantitative data was obtained from a questionnaire distributed to 96 respondents using the Skill Academy platform. The result of this study is that the constructs of system quality, information quality, and service quality have a positive effect on task-technology fit, and the task-technology fit construct has a positive effect on net benefits. In other words, the skills academy platform has quality systems, information, and services that allow tasks to be accommodated so that the impact is beneficial for users.